2023
DOI: 10.3389/fnins.2023.1171895
|View full text |Cite
|
Sign up to set email alerts
|

Fragile X Syndrome as an interneuronopathy: a lesson for future studies and treatments

Abstract: Fragile X Syndrome (FXS) is the most common form of inherited intellectual disability (ID) and a primary genetic cause of autism spectrum disorder (ASD). FXS arises from the silencing of the FMR1 gene causing the lack of translation of its encoded protein, the Fragile X Messenger RibonucleoProtein (FMRP), an RNA-binding protein involved in translational control and in RNA transport along dendrites. Although a large effort during the last 20  years has been made to investigate the cellular roles of FMRP, no eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…Individuals with FXS tend to exhibit increased neural responses re ected by increased ERP amplitudes to auditory stimuli compared to typically developed individuals, likely due to neural hyperexcitability (Ethridge et al, 2016;Tempio et al, 2023). The original results from the phase 2a clinical trial suggested BPN14770 reduced the ERP amplitude of the rst stimulus in a habituation pair.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with FXS tend to exhibit increased neural responses re ected by increased ERP amplitudes to auditory stimuli compared to typically developed individuals, likely due to neural hyperexcitability (Ethridge et al, 2016;Tempio et al, 2023). The original results from the phase 2a clinical trial suggested BPN14770 reduced the ERP amplitude of the rst stimulus in a habituation pair.…”
Section: Discussionmentioning
confidence: 99%
“…In autism spectrum disorders (ASD) it is assumed that a shift in the balance of excitatory and inhibitory neuronal activity (E/I-balance) represents the underlying mechanism 27,28 . Also in Fragile X syndrome, a monogenetic cognitive impairment syndrome that is the most common cause of ASD, studies hint at an altered E/I-balance 29,30 . These findings are backed up by the fact that patients often show altered glutamine and GABA levels.…”
Section: Distinct Functional Microarchitecture Characterized By Low-a...mentioning
confidence: 99%